Beobachtungen zu den Neologismen der Politik – demonstiert am Projekt „Wortwarte“ - Dubiec-Stach, Joanna (Studia Germanica Posnaniensia, 2018)
Formative specifics of the German language creates particular conditions for forming neologisms and the related linguistic creativity. The degree to which neologisms are formed in contemporary German can be for instance easily observed upon the ‘Wortwarte’ project. Some of the neologisms considered as such by the authors of the ‘Wortwarte’ project shall be discussed in this article. The object of the linguistic analysis are neologisms from the world of politics. During analysis some interesting aspects referring to the form and specifics of contemporary neologisms have been pointed out i.e. word class presented by the analysed neologisms, their construction (i.e formative models upon which they have been formed), their components (i.e. native or foreign elements constituting them) as well as their semantics.